Penampilan Produksi Hijauan Hasil Tumpangsari Arbila (Phaseolus lunatus) Berinokulum Rhizobium dan Sorgum (Sorghum bicolor) pada Jarak Tanam Arbila dan Jumlah Baris Sorgum - Koten, B B; Soetrisno, R D; Ngadiyono, N; Soewignyo, B (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2013)
The study was conducted to evaluate the forage production of arbila (Phaseolus lunatus) and sorghum (Sorghum bicolor) in intercropping grown on different spacing of arbila and number row of sorghum, and was designed as completely randomized design of factorial pattern with two factors. The first factor was the spacing of arbila (J) i.e. J1 (120 cm) and J2 (180 cm). The second factor was row number of sorghum (P) i.e. P1 (1 row), P2 (2 rows), P3 (3 rows) with 3 replications. The variables were dry matter (DM) production, organic matter (OM) production, crude protein (CP)production of forage, and Land Equivalent Ratio (LER). The results showed that highest DM production at J1P2 and J1P3 (5.33 and 4.53 tons/ha), highest OM production at J1P2 and J1P3 (5.33 and 4.57 tons/ha), highest CP production at J1P1, J1P2 and J1P3 (0.55, 0.77, and 0.55 tons/ha), and highest LER at J1P2 and J1P3 (2.53 and 2.38). It can be concluded that the intercropping arbila and sorghum at planting space of 120 cm with 2 and 3 row of sorghums between arbilas produces the best forage production as ruminant feed.Key words: Phaseolus lunatus, Sorghum bicolor, intercropping, spasing, row number, forage